A visão enciclopédica da semântica de frames: uma aproximação com a lexicografia - Morais, Ana Carla Assmann (Universidade do Vale do Rio dos Sinos, 2017)
The art of dictionary making has a long tradition. In particular, general monolingual dictionaries are used by speakers of a language to solve doubts concerning words spelling and meaning. From what regards word sense treatment and organization, these dictionaries follow a semasiological approach. The present thesis explores Frame Semantics (FILLMORE, 1982, 1985) and its encyclopedic conception of meaning by examining its usability for traditional lexicographical practice. Although Frame Semantics has been mostly applied to projects in Computational Lexicography, we advocate, as suggested by Ostermann (2014), that traditional lexicography can benefit from this theory. Thus, through the corpus-based analysis of the lexical unit mãe, we intend to evaluate to which extent Frame Semantics encyclopedic conception of meaning may contribute to lexicographical treatment of word meaning. In order to explore the suitability of Frame Semantics as a theoretical framework for lexicography, mãeis described in a twofold way: first, a semantic analysis of the lexical unit is carried out and the frames evoked by it are identified, using Lakoff’s cognitive models for mother (LAKOFF, 1987), FrameNetKinship and Giving Birthframes, and data extracted from NILC corpus; second, six entries of mãein general monolingual dictionaries are analyzed in search for traces of the frames identified in the previous stage of the analysis. For processing NILC corpus Sketch Engine main functionalities were used. Results from the analysis show that the lexical unit mãeevokes five frames –Nascimento (birth), Parentesco(kinship), Relação Conjugal (conjugal relationship), Genético (genetic), and Cuidados(nurture). This finding shows that dictionaries should include the knowledge covered by these structures in their entries.
Keywords: Lexicografia; Semântica de frames; Conhecimento enciclopédico; Lexicography; Frame semantics; Encyclopaedic knowledge; ACCNPQ::Lingüística, Letras e Artes::Lingüística